2012
DOI: 10.1103/physreva.85.012102
|View full text |Cite
|
Sign up to set email alerts
|

Maintaining quantum coherence in the presence of noise through state monitoring

Abstract: Unsharp measurements allow the estimation and tracking of quantum wave functions in real time with minimal disruption of the dynamics. Here we demonstrate that high-fidelity state monitoring, and hence quantum control, is possible, even in the presence of classical dephasing and amplitude noise, by simulating such measurements on a two-level system undergoing Rabi oscillations. Finite estimation fidelity is found to persist indefinitely after the decoherence times set by the noise fields in the absence of meas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 22 publications
1
32
0
Order By: Relevance
“…which generalize Eq. (11). Restricting ourselves to the subspace suppC i , we see that the operator C i acts as the identity operator on all vectors |ξ ∈ suppC i .…”
Section: B Analytical Solution For Rank-r Projectorsmentioning
confidence: 99%
See 1 more Smart Citation
“…which generalize Eq. (11). Restricting ourselves to the subspace suppC i , we see that the operator C i acts as the identity operator on all vectors |ξ ∈ suppC i .…”
Section: B Analytical Solution For Rank-r Projectorsmentioning
confidence: 99%
“…Since the conditional output state is non-linearly related with the input density operator, other non-trivial dynamics is possible including the emerging chaotic behavior [9,10]. Repetitive measurements enable maintenance of quantum coherence in the presence of noise [11] or acceleration of decoherence [12]. Repeated selective measurements are applicable in ground state cooling [13].…”
Section: Introductionmentioning
confidence: 99%
“…We have also shown earlier [8], that it is possible, in principle, to monitor (approximately) the dynamics (Rabi oscillations) of a single two-level quantum system in real time using unsharp measurements, or to estimate the Rabi frequency [9], while only weakly influencing the original dynamics. By using unsharp measurement estimation in conjunction * Electronic address: choudhary@ukzn.ac.za † Electronic address: konradt@ukzn.ac.za ‡ Electronic address: huys@csir.co.za with feedback, Vijay et al recently demonstrated stabilization of Rabi oscillations in a superconducting qubit at a desired frequency [10].…”
Section: Introductionmentioning
confidence: 58%
“…However, to fulfill condition Eq. (22) excess of F = 0.999 [8]. However, several further imperfections need to be considered.…”
Section: Classical Dephasing Noisementioning
confidence: 99%
“…The state estimate * konradt@ukzn.ac.za † hermann.uys@gmail.com is sequentially updated based on the outcome of each measurement on the actual quantum state with the same propagator as the system. Numerical simulations have demonstrated the convergence of the state estimate when all parameters in the Hamiltonian are precisely known [4,14] and even for the case of process tomography, treating the Hamiltonian parameters as state variables of a hybrid system [15][16][17].…”
Section: Introductionmentioning
confidence: 99%